Nutritional profile of hemodialysis patients concerning treatment time - Alvarenga,Livia de Almeida (2017)
Abstract Introduction: The mortality of the population with chronic kidney disease (CKD) on hemodialysis (HD) is very high and the protein-energy malnutrition stands out as one of the most common consequences in relation to this condition. Objective: To evaluate the association between time of hemodialysis and nutritional parameters of patients. Methods: It is a cross-sectional study with secondary data, developed of the University Hospital of the Federal University of Juiz de Fora (HU/UFJF). This study was approved by the Research Ethics Committee (Nº 1.233.142), a total of 36 patients. The medical records and collected data were analyzed for anthropometric markers, biochemical and diet, considering two groups: HD time less than three and greater than or equal to three years. Results: There was reduction of mass of somatic protein with increased duration of HD. In relation to food intake was observed that in patients with increased duration of dialysis, an increase in average consumption of protein / kg of weight, calories, phosphorus and potassium, with a significant difference from the mean protein intake / kg (p = 0.04) and phosphorus (p = 0.045). Increasing HD time has altered body composition of patients, indicating a decline in the nutritional status of these individuals. Conclusion: HD patients are a risk group for protein-energy malnutrition, where HD time interferes with the nutritional status and food profile of the patient. The group HD time greater than or equal to 3 years presented worsening nutritional status.